Synthesis and luminescence properties of La2Zr2O7:R (R = Sm3+, Bi3+, Sm3+/Bi3+) phosphor. (July 2018) - Cao, Renping; Quan, Guanjun; Shi, Zhihui; Chen, Ting; Luo, Zhiyang; Zheng, Guotai; Hu, Zuofu
Abstract: La2 Zr2 O7 :R (R = Sm 3+, Bi 3+, Sm 3+ /Bi 3+ ) phosphors are synthesized by solid-state reaction method in air. Blue emission band peaking at ∼462 nm of La2 Zr2 O7 :Bi 3+ phosphor with excitation at 312 nm is observed in the range of 370–610 nm due to 3 P 1 → 1 S 0 transition of Bi 3+ ion and D → 1 S0 transition between Bi 3+ and Zr 4+ ions. La2 Zr2 O7 :Sm 3+ phosphor with excitation at 407 nm shows reddish orange light in the range of 550–750 nm owing to 4 G5/2 → 6 H J ( J = 5/2, 7/2, 9/2, and 11/2) transitions of Sm 3+ ion. Tunable emission from blue to white of La2 Zr2 O7 :Sm 3+, Bi 3+ phosphor with excitation at 312 nm can be observed due to the changing Bi 3+ or Sm 3+ ion concentration. La2 Zr2 O7 :Sm 3+, Bi 3+ phosphor with excitation at 407 nm only emits reddish orange because Bi 3+ has no absorption at 407 nm. The energy transfer from Bi 3+ to Sm 3+ is discussed. The luminous mechanism is explained by the energy level diagrams of Bi 3+ and Sm 3+ ions. Graphical abstract: Highlights: La2 Zr2 O7 :Sm 3+, Bi 3+ phosphors are synthesized by solid-state reaction method in air. La2 Zr2 O7 :Bi 3+, La2 Zr2 O7 :Sm 3+, and La2 Zr2 O7 :Sm 3+, Bi 3+ phosphors are compared and analyzed. The luminous mechanism is explained by the energy level diagrams of Bi 3+ and Sm 3+ ions.